Local Wisdom of Cirebon Ethnic Megamendung Batik Motifs in the Context of Ethnopedagogy - Rohmah, Aulia; Elayna Rahmasari; Yachinta Diana Sari Susanti; Iin Wariin Basyari; Iis Yeni Sugiarti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Local wisdom in the form of Cirebon ethnic megamendung batik has great potential to be integrated into learning in elementary schools, but currently its application is still limited. This research aims to analyze the symbolic meaning and values ​​contained in megamendung batik and identify the material content that can be conveyed in science and science learning. Qualitative methods with a micro ethnographic approach were used in this research, with data collection techniques in the form of observation, documentation studies and in-depth interviews. The results of this research are that megamendung has symbolic meaning and values ​​contained in the batik. The symbolic meaning contained is that we as humans, when we are at the top, must always protect our fellow citizens. The values ​​contained in the Megamendung batik motif are Islamic values, moral values ​​and artistic values. From the results of this research, it can be concluded that megamendung can be used as a learning resource. Through megamendung batik, several material contents can be conveyed, including history, values ​​such as moral values, Islam, which can be seen from the motifs, colors and structures of the batik. Then the next material content can be delivered through a project, namely drawing and coloring Megamendung batik motifs